Saturated Fat Acid Food Consumption Correlation with Hypertension in Elderly Woman (Indian Journal of Public Health Research & Development, 2020)
Context: Hypertension is a disease often encountered in the elderly. This occurs due to physiological andlifestyle changes including eating habits. Food consumption habits of high cholesterol sources can resultin the accumulate of fat in blood vessels and forming plaque. It result in an increase in blood pressure thatleads to hypertension. The purpose of this research is to analyze the correlation of food consumption habitssaturated fat sources with hypertension in elderly woman.This study uses case control design with sample of elderly female in Health Centre Gunung Anyar Surabaya.Subject consisting of 28 cases and 28 controls. Data food consumption of saturated fat obtain through recallmethod Semi Quantitative Food Frequency Questionnare (SQ-FFQ). Blood pressure is measured usingsphygnomanometer. The statistical test performed is the chi square test.The result showed that there was a significant relationship between food consumption saturated fat acidsources with hypertension among elderly woman (p = 0,01).The conclusion of this study is that there is a significant relationship between the food consumption ofsaturated fat acid with hypertension in elderly women.
Keywords: Hypertension, saturated fat acid, elderly woman